A Now You See Me: Discussing Youth Privacy Paradox and Contextual Integrity in TikTok - Azmi Firdhausi; Mufti Nurlatifah (Universitas Multimedia Nusantara, 2025)
Privacy has emerged as a critical subject for media and communication research, especially with the youth's growing use of TikTok as a social networking site. This study aims to describe privacy among active young TikTok users through the perspective of the Contextual Integrity Privacy Theory by Helen Nissenbaum and the Privacy Paradox. This study adopts a qualitative research approach and a single case study. This research was analyzed through in-depth interviews with seven TikTok users aged 15-24. The findings reveal how youth navigate privacy concerns in their data practices, highlighting the role of contextual integrity in shaping their decisions. Participants demonstrated an acute awareness of privacy risks and employed strategies such as selective sharing, pseudonym use, and engagement with privacy tools to safeguard personal information. However, the study also highlights the persistence of the privacy paradox, where the desire for social validation often conflicts with privacy behaviors. These insights contribute to the theoretical discourse on privacy and offer practical recommendations for robusting safer and more transparent digital environments for youth.